Identification of the sharing contribution of the power supply system power sources to the electricity losses and their cost - A. V. Malafeev (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Consider the problems of estimating the cost of services for the transmission of electricity through the electric networks of territorial grid organizations (TGOs), including large industrial enterprises with the status of TGOs and their own generation. Develop a methodology for calculating the cost of electricity losses in the elements of the power supply system of such enterprises, taking into account the technical and economic characteristics of the sources. Develop a methodology for determining the share contribution of individual sources and consumers to electricity losses and their cost. Calculate the cost of electricity losses and the structure of the contribution to it of power sources of an industrial TGO enterprise and draw conclusions. METHODS. When solving the tasks set, methods for calculating steady-state modes of power supply systems were used. RESULTS. The article describes the relevance of the topic, created calculation methods, in the conditions of a large industrial power center, the system of payment by sub-subscribers of an industrial enterprise for services for the transmission of electricity and its relationship with the flow distribution is considered. The structure of the contribution of power sources to the losses of electricity in the power supply system is analyzed. An approach has been formulated to adjust the individual tariff for the purchase of electricity losses, taking into account the placement of power sources in the power supply system. Recommendations are given to reduce the degree of undercompensation of the cost of electricity transmission services by third-party consumers. It is proposed to use for these purposes the norms of technological losses of electricity (NTLE), determined by the cost of losses. CONCLUSION. Under the current regulatory framework, it is in the interests of TGO enterprises to distribute sub-subscribers in the scheme in such a way that their actual NTLE, determined taking into account the targeting of losses, does not exceed the calculated NTLE. In this case, there is no transfer of the cost of losses from sub-subscribers to the own consumption of the TGO enterprise. At the same time, sub-subscribers do not incur additional costs, since they pay off with the guaranteeing supplier at the boiler tariff. NTLE for these purposes must be determined by the cost of losses, taking into account the characteristics of the sources. The share of payment for losses in the networks of an TGO enterprise, which goes to its own consumption and is not compensated by sub-subscribers, is reduced. Consequently, the amount of costs for electricity and their share in the cost of finished products of the TGO enterprise is reduced.